FABRIKASI DAN KARAKTERISASI ELEKTRODA KARBON UNTUK SISTEM DESALINASI LARUTAN KCl DENGAN METODE FREEZING THAWING - Sari, Intan Permata; Endarko, Endarko (BERKALA FISIKA, 2015)
Carbon electrode using an active carbon and poly(vinylalcohol) PVA binder (a water-soluble polymer) by freezing thawing have successfully been synthesized and characterized. In this research, synthesis of carbon electrode was used freezing thawing method with 4 cycles. For each one cycle is required 12 hours for freezing and 12 hours for thawing. Specific capacitance of carbon electrode has been observed and measured using cyclic voltammetry and resulted in a value of 9.1 F/g. Meanwhile, SEM image of the cross-section of electrode showed that the electrode has enough pores so that can be used as electrode in a capacitive deionization system. . Desalination experiments were carried out in single-pass mode. KCl solution with an initial conductivity of 180μs/cm is pumped to CDI cell with ﬂow rate of 25 mL/min at voltage source of 2 V. The result showed that the percentage value of the salt-removal was achieved at 64.95%. Keywords: PVA, activated carbon, capacitive deionization, cyclic voltammetry, desalination